VYC-25L Hyaluronic Acid Injectable Gel Is Safe and Effective for Long-Term Restoration and Creation of Volume of the Lower Face. (21st January 2020) - Ogilvie, Patricia; Benouaiche, Laurence; Philipp-Dormston, Wolfgang G; Belhaouari, Lakhdar; Gaymans, Frodo; Sattler, Gerhard; Harvey, Candice; Schumacher, Andrew
Abstract: Background: Juvéderm Volux (VYC-25L; Allergan plc) is an injectable hyaluronic acid gel designed to restore and create facial volume. Objective: The aim of this study was to evaluate the safety and effectiveness of Volux for chin retrusion over 18 months and after repeat treatment. Methods: This prospective, single-blind, controlled study enrolled subjects aged ≥18 years with chin retrusion (glabella-subnasale-pogonion facial angle 145°-165°). Subjects were randomized (3:1) to Volux at study onset or 3 months later (control group), and could receive a single repeat treatment during months 18 to 24. Assessments included mean facial-angle change from baseline, Global Aesthetic Improvement Scale (GAIS) responder rates (improved/much improved), improvements in 3 subject-reported FACE-Q scales, and safety. Results: Of 132 enrolled subjects, 119 received initial Volux treatment and 89 received repeat treatment. Mean changes (95% confidence interval) in glabella-subnasale-pogonion angle from baseline for treatment and control groups, respectively, were: 1.15° (0.75°, 1.56°) and 1.16° (0.57°, 1.75°) at month 18, and 3.14° (2.68°, 3.61°) and 2.72° (1.78°, 3.66°) 1 month after repeat treatment. Investigators rated 52.5%/60.0% of treated/control subjects at month 18 and 96.9%/100% after retreatment as GAIS responders; subject-reported rates were 62.0%/64.0% and 93.8%/100%. Durable improvements in Satisfaction with Chin, Satisfaction with Lower Face and Jawline, and Psychological Well-Being were reported in 82.1%, 78.2%, and 60.3% of subjects, respectively, at month 18, and 92.3%, 93.8%, and 67.7% of subjects after retreatment. The safety profile was as expected. Conclusions: Volux injectable gel is a safe, effective, and durable alternative to surgical treatments for increasing chin projection and jaw volume, and results in high patient satisfaction. Level of Evidence: 2: